Examining the efficiency of electrochemical purification of storm wastewater at machinebuilding enterprises - Maksimenko, Olena; Pancheva, Hanna; Madzhd, Svitlana; Pysanko, Yana; Briankin, Oleksandr; Tykhomyrova, Tetyana; Hrebeniuk, Tatiana (Eastern-European Journal of Enterprise Technologies, 2018)
We have examined the composition of polluted storm water discharged from the territory of a machinebuilding enterprise. It was established that the territory was unevenly polluted, with the surface wastewater from the area adjacent to the production shops dominated by ions of copper, to 1.1 mg/dm3; zinc, to 2.0 mg/dm3; nickel, to 1.6 mg/dm3; chromium, to 0.93 mg/dm3, and lead, to 5.0 mg/dm3. It was found that the removal of metals’ ions during electrocoagulation treatment is significantly influenced by the following factors: a flow rate of the wastewater sent for purification; duration of wastewater settling upon electrocoagulation, and current density during electrolysis. We have defined optimal parameters for the wastewater treatment process. Based on experimental research, we have built graphic dependences of purification effectiveness on current density and water settling time. The optimal parameters were determined for the wastewater treatment process, which ensure sufficiently high efficiency of water purification from heavy metals’ ions (to match the values for discharge standards) at an acceptable amount of electricity. It was established that the best conditions for deposition of nickel and lead are a current density of 50 A/m3 and a time of settling after electrocoagulation of 9 hours. The optimal conditions for depositing copper and zinc are 12 hours, and it is possible to lower the concentration of chromium to safe concentrations at a current density of 10 A/m3 and a time of settling of 4 hours. It was revealed that the effectiveness of purification from metals’ ions increases significantly with an increase in the current density and settling time; in addition, the efficiency of settling is 1.4‒3 times higher than the increase in current density. It is shown that prolonging the time of settling might not always compensate for the decrease in current density during electrocoagulation, which requires selecting the optimal balance of all factors. The experimental data that we acquired are necessary to calculate the technological process parameters. By applying a method of fullfactor experiment, we have constructed mathematical models of the process, which include the dependence of response (the residual concentration) on the aboveenumerated factors. The proposed models could make it possible to control the process of electrocoagulation by influencing those factors on which the efficiency of purification depends